THE EFFECT OF PRICE DISCOUNTS, PRODUCT QUALITY, AND DIGITAL PROMOTIONS ON CUSTOMER SATISFACTION (CASE STUDY OF GOFOOD USERS IN JEMBER AREA) - Amiliya, Nafia Nanda; Hermawan, Haris; Nursaidah, Nursaidah (Univesitas Muhammadiyah Tangerang, 2024)
Along with increasing economic growth, MSMEs are encouraged to be more active, creative and innovative in trade. Trading via social media makes things easier for consumers with fast access and easy payments. Currently, smartphone technology facilitates access to applications such as Gojek which can be downloaded on Playstore, Gojek offers online services including Gofood. Gofood offers fast and efficient food delivery, making it easier for users to continue using Gofood features. This research aims to determine the effect of price discounts, product quality and digital promotions on customer satisfaction of Gofood users in the Jember area. This research uses associative techniques with a quantitative approach. The sample in this study consisted of 100 Gofood users in the Jember area. The sampling technique here uses non-probability sampling with a purposive sampling approach. Data collection techniques used literature studies and questionnaires. The hypothesis test from this research uses a partial test (t test) and is calculated using SPSS 22. The results of this research show that price discounts (X1), product quality (X2), and digital promotions (X3) partially have a positive and significant effect on satisfaction. customers of Gofood users in the Jember area.